Laparoscopic rectal cancer surgery: Where do we stand? - Krane, Mukta K (Baishideng Publishing Group Co., Limited, 2012)
Large comparative studies and multiple prospective randomized control trials (RCTs) have reported equivalence in short and long-term outcomes between the open and laparoscopic approaches for the surgical treatment of colon cancer which has heralded widespread acceptance for laparoscopic resection of colon cancer. In contrast, laparoscopic total mesorectal excision (TME) for the treatment of rectal cancer has been welcomed with significantly less enthusiasm. While it is likely that patients with rectal cancer will experience the same benefits of early recovery and decreased postoperative pain from the laparoscopic approach, whether the same oncologic clearance, specifically an adequate TME can be obtained is of concern. The aim of the current study is to review the current level of evidence in the literature on laparoscopic rectal cancer surgery with regard to short-term and long-term oncologic outcomes. The data from 8 RCTs, 3 meta-analyses, and 2 Cochrane Database of Systematic Reviews was reviewed. Current data suggests that laparoscopic rectal cancer resection may benefit patients with reduced blood loss, earlier return of bowel function, and shorter hospital length of stay. Concerns that laparoscopic rectal cancer surgery compromises short-term oncologic outcomes including number of lymph nodes retrieved and circumferential resection margin and jeopardizes long-term oncologic outcomes has not conclusively been refuted by the available literature. Laparoscopic rectal cancer resection is feasible but whether or not it compromises short-term or long-term results still needs to be further studied.